2015
DOI: 10.1002/hbm.23058
|View full text |Cite
|
Sign up to set email alerts
|

Hindbrain regional growth in preterm newborns and its impairment in relation to brain injury

Abstract: Premature birth globally affects about 11.1% of all newborns and is a risk factor for neurodevelopmental disability in surviving infants. Histology has suggested that hindbrain subdivisions grow differentially, especially in the third trimester. Prematurity-related brain injuries occurring in this period may selectively affect more rapidly developing areas of hindbrain, thus accompanying region-specific impairments in growth and ultimately neurodevelopmental deficits. The current study aimed to quantify region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
6
15
1
Order By: Relevance
“…We have recently reported that cerebellar hemorrhage are associated with impaired cerebellar growth in preterm newborns. 22 Limperopoulos et al have shown that cerebellar injury in preterm newborns is associated with impaired growth of specific cerebral regions, 23 which in turn is associated with regional-specific functional deficits. 39 Taken together, these studies suggest that cerebellar hemorrhage may lead to neurodevelopmental disabilities through disruption of cerebellar-cortical connections secondary to impaired cerebellar growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that cerebellar hemorrhage are associated with impaired cerebellar growth in preterm newborns. 22 Limperopoulos et al have shown that cerebellar injury in preterm newborns is associated with impaired growth of specific cerebral regions, 23 which in turn is associated with regional-specific functional deficits. 39 Taken together, these studies suggest that cerebellar hemorrhage may lead to neurodevelopmental disabilities through disruption of cerebellar-cortical connections secondary to impaired cerebellar growth.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of this cohort was included in our prior study of the association between cerebellar hemorrhage and cerebellar volume (n=56). 22 Parental consent was obtained following a protocol approved by the UCSF Committee on Human Research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects upon brain growth may differ in the presence of different perinatal clinical conditions such as preterm birth (Padilla et al, 2015), low body weight at birth (Parikh et al, 2013), prematurity-related brain injuries (Kim et al, accepted for publication; Kim et al, 2016; Tam et al, 2011b), and the related treatments (Tam et al, 2011a). Cortical folding may also be impaired as a result of such clinical factors (Engelhardt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using a variety of volumetric techniques, it has been shown that cerebellar growth is affected by supratentorial injury such as IVH, whereas WMI showed no association [27]. Evaluating the growth of the entire hindbrain, Kim et al [28] found that moderate-to-severe IVH did indeed slow growth and this was also seen with severe cerebellar hemorrhage.…”
Section: Preterm Brain Injurymentioning
confidence: 99%